1996
DOI: 10.1097/00005768-199607000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of ??VO2 in older individuals with osteoarthritis of the knee and cardiovascular disease

Abstract: The American College of Sports Medicine (ACSM) equation for estimating oxygen consumption (VO2) is often inappropriately applied to non-steady-state treadmill exercise. Therefore, it was the purpose of this investigation to develop an equation to estimate VO2 that could be applied to non-steady-state treadmill exercise in a population of patients with osteoarthritis of the knee, and to assess the generalizability of this equation for estimating VO2peak in patients with cardiovascular disease. Subjects for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Potential participants were excluded if they met any of the following criteria: 1) serious medical condition that prevented safe participation in an exercise program, including symptomatic heart or vascular disease (angina, peripheral vascular disease, congestive heart failure), severe hypertension, recent stroke, chronic obstructive pulmonary disease, severe insulin‐dependent diabetes mellitus, psychiatric disease, renal disease, liver disease, active cancer other than skin cancer, and anemia; 2) a Mini‐Mental State Examination score of <24; 3) inability to finish the 18‐month study or unlikely to be compliant; 4) inability to walk without a cane or other assistive device; 5) participation in another research study; 6) reported alcohol consumption of >14 drinks per week; 7) ST segment depression of at least 2 mm at an exercise level of 4 METS or less, hypotension, or complex arrhythmias during a graded exercise test (36); 8) inability to complete the protocol, in the opinion of the clinical staff, because of frailty, illness, or other reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Potential participants were excluded if they met any of the following criteria: 1) serious medical condition that prevented safe participation in an exercise program, including symptomatic heart or vascular disease (angina, peripheral vascular disease, congestive heart failure), severe hypertension, recent stroke, chronic obstructive pulmonary disease, severe insulin‐dependent diabetes mellitus, psychiatric disease, renal disease, liver disease, active cancer other than skin cancer, and anemia; 2) a Mini‐Mental State Examination score of <24; 3) inability to finish the 18‐month study or unlikely to be compliant; 4) inability to walk without a cane or other assistive device; 5) participation in another research study; 6) reported alcohol consumption of >14 drinks per week; 7) ST segment depression of at least 2 mm at an exercise level of 4 METS or less, hypotension, or complex arrhythmias during a graded exercise test (36); 8) inability to complete the protocol, in the opinion of the clinical staff, because of frailty, illness, or other reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, inclusion criteria included: (1) age ≥ 60 years; (2) overweight or obese (BMI ≥ 28.0 kg*m −2 ); (3) radiographic evidence in one or both knees of Kellgren-Lawrence grade I-III tibiofemoral OA in weight-bearing anteroposterior view and/or patellofemoral OA in sunrise view; (4) no more than 20 minutes of regular exercise per week; (5) self-report of knee pain on most days of the month; (6) self-report of difficulty due to knee pain in one or more daily activities (e.g., walking one-quarter mile, shopping, bending, etc); and (7) willingness to undergo testing and intervention procedures. Exclusion criteria included: (1) serious co-morbid medical condition that could prevent safe participation in an exercise program; (2) score of < 24 on Mini-Mental State Exam (MMSE); (3) inability or unwillingness to modify dietary and/or exercise behaviors; (4) inability to complete the 18-month study or probability of noncompliance; (5) inability to walk without a cane or other assistive device; (6) participation in another interventional research study; (7) self-reported alcohol consumption of > 14 drinks per week; or (8) ST-segment depression of > 2 mm at an exercise level of 4 METs or less, hypotension or complex arrhythmias during a graded exercise test (16). …”
Section: Methodsmentioning
confidence: 99%
“…All tests were conducted using a modified Naughton procedure (Berry et al, 1996). A Quinton 3000B EKG was used during the test to monitor heart function and a physician was present during the testing.…”
Section: Maximal Oxygen Consumption (Vo 2 Max ) Testmentioning
confidence: 99%